2020
DOI: 10.2147/idr.s224238
|View full text |Cite
|
Sign up to set email alerts
|

<p>Differentiation of Intraspinal Tuberculosis and Metastatic Cancer Using Magnetic Resonance Imaging</p>

Abstract: This study aimed to explore the differences in the magnetic resonance imaging (MRI) findings between intraspinal tuberculosis and metastatic cancer, which may aid in making the correct diagnosis. Patients and Methods: The clinical features and MRI findings of 15 patients with intraspinal tuberculosis and 11 patients with intraspinal metastatic cancers were retrospectively analyzed. Results: The mean ages of the patients with intraspinal tuberculosis and metastatic cancer were 26.3 (15-42) and 52.1 (38-67) year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Tuberculous leptomeningitis with intraspinal nodules was considered one of the most common features. In the study by Li et al (2020) T1-W1-weighted imaging showed thickened meninges. At the same time, Saxena et al (2021) found no enhancement of leptomeningitis in a few patients.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Tuberculous leptomeningitis with intraspinal nodules was considered one of the most common features. In the study by Li et al (2020) T1-W1-weighted imaging showed thickened meninges. At the same time, Saxena et al (2021) found no enhancement of leptomeningitis in a few patients.…”
Section: Discussionmentioning
confidence: 77%
“…Involvement of vertebral body, lamina, pedicles, and spinous was seen more in the metastatic spine (75% of metastasis and 70% of Pott's spine cases) (Garg & Somvanshi, 2011). Whereas in the study by Li, et al (2020), it was found that in 5 of 15 spinal tuberculosis patients, the affected side was the thoracic region, in five patients the lumbar and sacral regions, and in five other patients more than two spinal cord regions were involved. Metastasis with each thoracic and lumbar lesion was seen in one of eleven patients, with one instance impacting the whole spinal cord and the other nine affecting more than two locations (Mertaniasih, et al, 2019).…”
Section: Results Study Selectionmentioning
confidence: 85%
See 2 more Smart Citations
“…The lesion of intraspinal tuberculoma can exist in epidural, intradural, and intramedullary space, causing spinal cord compression. Due to the distribution of blood supply to spinal cord, thoracic segment receives nearly 45% of spinal cord blood supply resulted in intraspinal tuberculoma was most commonly found in the thoracic segments 11 . Our patient is a 31-year-old male with a history of tuberculosis of pulmonary and intestinal, MRI and CT images of the spine demonstrated a contrast-enhancing extradural lesion with vertebral body destruction at T2–T4 causing significant spinal cord compression.…”
Section: Discussionmentioning
confidence: 99%